Multiuse of Disposable Microsurgical Instruments as a Cost-Efficient Alternative for Training and Research. Issue 5 (May 2017) - Aman, Martin; Sporer, Matthias E.; Riedl, Otto; Wang, Wei-Te; Kramer, Anne; Aszmann, Oskar C.; Bergmeister, Konstantin D.
Abstract : Summary: Microsurgery demands significant preclinical training, often hampered by the high costs of the required microsurgery instruments. We hypothesized that recently available disposable microsurgery instruments provide sufficient quality and significantly reduced costs. In a comparative analysis with standard reusable instruments, participants performed equally with both instrument sets and recommended the disposable instruments for microsurgery training and research applications. Abstract : Supplemental Digital Content is available in the text.